Facultad de Ciencias Administrativas realizó su Casa Abierta para difundir su oferta académica - García García, Mariana (2023)
As part of the festivities of the State University of Bolívar, which turns 34 years old of autonomous living, the Faculty of Administrative Sciences, Business Management and computer science, organized the Open House to disseminate the careers it has within its Academic Offer. Thus, the careers of: Human Talent; Accounting and auditing; Administration of Companies; Marketing; Communication; Turism and hotelery; Entrepreneurship and Social Innovation and Software, through each stand they demonstrated the skills that they have in their professional training.